Real-time measurement of cerebral blood flow during and after repetitive transcranial magnetic stimulation: A near-infrared spectroscopy study - Park, Eunhee; Kang, Min Jae; Lee, Ahee; Chang, Won Hyuk; Shin, Yong-Il; Kim, Yun-Hee (Neuroscience letters, 2017)
•Hz rTMS influenced changes of cerebral blood flow in the unstimulated hemisphere.•The stimulated M1 influenced the level of oxyhemoglobin in both unstimulated M1 and PM.•It seemed to constitute a function of interhemispheric modulation of rTMS. To confirm the interhemispheric modulation induced by low-frequency repetitive transcranial magnetic stimulation (rTMS) over the primary motor cortex, real-time regional cerebral blood flow (rCBF) was assessed using functional near-infrared spectroscopy (fNIRS) in the contralateral primary motor cortex (M1) and premotor cortex (PM). Ten right-handed healthy subjects completed two experimental sessions that were randomly arranged for real or sham rTMS session. In the real rTMS session, fNIRS data were acquired from the right M1 and PM area, while the motor hot spot of the left M1 was stimulated with 1Hz rTMS for 1200 pulses with two boosters. In the sham stimulation session, stimulation was delivered with a disconnected coil. During the real rTMS session, the concentration of oxyhemoglobin ([oxy-Hb]) in the right M1 increased continuously until the end of the stimulation. These changes lasted for 20min, while the right PM did not show a change in [oxy-Hb] concentration. On the other hand, the concentration of deoxy-hemoglobin ([deoxy-Hb]) decreased continuously in the right M1 and PM during the real rTMS stimulation, and this change lasted for 20min after the stimulation. The sham stimulation did not exhibit any significant change in both [oxy-Hb] and [deoxy-Hb] concentration during or after the stimulation. Application of 1Hz rTMS over M1 resulted in changes of rCBF in contralateral M1 and PM, which seemed to constitute a function of interhemispheric modulation of rTMS. The fNIRS data was able to detect this physiological change of neuromodulatory action of rTMS in real-time.